Factors Influencing Teacher Motivation to Become School Principal in Serang City - Syafrudin, Syafrudin; Hufad, Achmad; Fathurrohman, Maman (Tarbawi, 2021)
The value of recruiting and maintaining highly trained school leaders is rising in our country. This research aimed to determine factors that teacher’s motivation being school principals. The survey responses of 104 public school principals in Serang City, including 77 elementary school principals and 27 junior high school principals, were evaluated using exploratory factor analysis. According to the results, factors such as Challenge, Altruism, Professional Advantage, and Leadership Influence encourage teachers to move into administration. In contrast, factors such as Inadequate Gain/Personal Benefit, Personal Needs or Issues, and Elevated Risk deter teachers from being school principals.